All-Russian Symposium “Milestones of History” - Giniyatullina L.S. (Золотоордынское обозрение)
On October 12–14, 2023 the All-Russian (with international participation) symposium “Milestones of History” was held in the Chelyabinsk region. Four round tables were held within the framework of symposium: “Ulus of Jochi, time of formation: 1207–1243” (October 12, Varna village), “Mausoleums of the Middle Ages of the Volga-Urals, Crimea and Kazakhstan: research of problems” (October 12, Varna village), “Southern and Middle Urals from Jochi to Nicholas I” (October 13, Chelyabinsk) and “History, economics and culture of the medieval Turkic-Tatar states of Western Siberia” (October 14, Chelyabinsk).